Reporting guidelines and a touch of critical appraisal - Pilar Aizpurua Galdeano; Paz González Rodríguez; María Aparicio Rodrigo; Nieves Balado Insunza; Elena Pérez González; Juan Ruiz-Canela Cáceres; Eduardo Ortega Páez (Elsevier, 2023)
The biomedical research process must follow certain quality criteria in its design and development to ensure that the results are credible and reliable. Once completed, the time comes to write an article for publication. The article must present in sufficient detail, and in a clear and transparent manner, all the information on the research work that has been carried out. In this way, readers, after a critical reading of the published content, will be able to judge the validity and relevance of the study and, if they so wish, make use of the findings.In order to improve the description of the research process for publication, a series of guidelines have been developed which, in a simple and structured way, guide authors in the preparation of a manuscript. They are presented in the form of a list, flowchart, or structured text, and are an invaluable aid when writing an article.This article presents the reporting guidelines for the most common designs along with the corresponding checklists. Resumen: El proceso de investigación biomédica debe seguir unos criterios de calidad en su diseño y elaboración, que garanticen que los resultados son creíbles y fiables. Una vez finalizado, llega el momento de escribir un artículo para su publicación. Este debe presentar con suficiente detalle, y de forma clara y transparente, toda la información del trabajo de investigación realizado. De esta forma, los lectores, tras una lectura crítica de lo publicado, podrán juzgar la validez y la relevancia del estudio, y si lo consideran, utilizar los hallazgos.Con el objetivo de mejorar la descripción del proceso de investigación para su publicación, se han desarrollado una serie de guías que, de forma sencilla y estructurada, orientan a los autores a la hora de elaborar un manuscrito. Se presentan en forma de lista, diagrama de flujo, o texto estructurado, y son una ayuda inestimable a la hora de escribir un artículo.Este artículo presenta las guías de elaboración de manuscritos de los diseños más habituales, con sus listas de verificación.